Regrowth mechanism for oxide isolation of GaAs nanowires. (4th September 2017) - Dvorak, David; Darbandi, Ali; Kavanagh, Karen L; Watkins, Simon P
Abstract: Oxide-isolated GaAs nanowires (NWs) were obtained through a lithography-free method in which axial growth of NWs coated in aluminum oxide (Al2 O3 ) is restarted using an annealing step. NWs are grown using the vapor–liquid–solid method and coated in nanometer thin oxide films using atomic layer deposition. Continued growth at the oxide-coated nanoparticle (NP) occurs after the thermally-induced fracture of the oxide during annealing. This oxide fracture is observed to depend on NP diameter, oxide thickness and annealing temperature. A thermal expansion mismatch model for stresses on the oxide shell is put forward to explain these results.